Transcranial direct current stimulation is not effective in the motor strength and gait recovery following motor incomplete spinal cord injury during Lokomat® gait training. (4th May 2016) - Kumru, Hatice; Murillo, Narda; Benito-Penalva, Jesus; Tormos, Jose M.; Vidal, Joan
Highlights: This is a first study showing tDCS effect on lower extremity motor strength and gait in motor incomplete spinal cord injury patients. With twenty daily sessions of tDCS, there was an expected improvement in motor strength and gait, however, did not differ between patients treated with anodal or sham tDCS. Abstract: Objective/Hypothesis: Transcranial direct current stimulation (tDCS) is a potential tool to improve motor recovery in patients with neurological disorders. Safety and efficacy of this procedure for lower extremity motor strengthe and gait function in motor incomplete spinal cord injury (SCI) have not yet been addressed. The aim of this study is to optimize the functional outcome in early phases of gait rehabilitation assisted by Lokomat ® in motor incomplete SCI patients using tDCS as an additional treatment to physical therapy. Methods: We performed in a SCI unit a single-centre randomized, double-blind, sham-controlled study to investigate safety and efficacy of anodal tDCS of over leg motor cortex in motor incomplete SCI patients. Twenty-four SCI patients received either daily sessions of anodal tDCS (n = 12) at 2 mA for 20 min to the vertex (leg motor cortex) during twenty days or sham tDCS (n = 12). Motor deficit was assessed by the lower extremity motor score (LEMS) and for gait function: ten meter walking test (10 MWT) and Walking Index for SCI (WISCI II) at baseline, after last tDCS session (after 4 weeks of stimulation), and after 8 weeks (from baseline) for follow-up. Results: No side effects were detected during either tDCS or sham. In both groups, there was a significant improvement in LEMS (p < 0.03), which did not significantly differ when comparing anodal and sham tDCS groups. During follow-up, in both group 5 of 12 patients could perform gait, without significant differences in gait velocity, cadence, step length and WISCI-II between both groups. Conclusion: Combination twenty sessions of daily tDCS to the leg motor cortex and Lokomat ® gait training appear to be safe in motor incomplete SCI patients. There was an expected improvement in both LEMS and gait scales however, did not differ between patients treated with anodal or sham tDCS.